(3UhQ GdCbGdje GdSHYIs - (3CMeO Hf Sgd GdHdNj, CHh RjO GdHdNj,J (B322 (3g` s
(3ChdgG (B:s
"(3aEfi PcQJ ai cJGHi gPG CbGdje GdCQV Ydi GdeeGdc hbUOJ efgG HdGO GdESdGe HJaUjd eOfgG , hJbSje eG jYhO HGdCYeGd GdeLehYI EdjgG hde CbUO GdCbGdje GdJi YdjgG bSeI GdCQV , Hd LYdJ cd bWYI s
(3HChdgG dhMJGf ePgJGf cJH ai WQI GMOGgeG YfhGf GdcJGHs
(3efbhdg ef fSNI ZGjI GdUMIs
(3cJH HQSe GdSdWGf eMeO Hf eQGO NGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B134s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B23 - (3U (B563 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1084s
Keywords: (3GdLZQGajG h GdHdOGfs